Answer:
The answer is B. Acute isosceles
(x1,y1)
(x2,y2)
(xm,ym)
Midpoint formula is given as below.
((x1 + x2)/2 , (y1 + y2)/2 )
Where
(x1 + x2)/2 = xm ----------- (1)
(y1 + y2)/2 = ym ----------- (2)
Equation (1) implies that;
x1 + x2 = 2xm
x2 = 2xm – x1
Equation (2) implies that;
y1 + y2 = 2ym
y2 = 2ym – y1
Thus the end point is
<span>(x2,y2) = (2xm – x1, 2ym – y1)</span>
Has to multiply I think try that !
Answer:
1/6
Step-by-step explanation:
1/3 diveded by 2/1
1/3x1/2 = 1/6
Hope it helps:)
Answer:
7. r = -5
8. x = -1
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define</u>
r + 2 - 8r = -3 - 8r
<u>Step 2: Solve for </u><em><u>r</u></em>
- Combine like terms: -7r + 2 = -3 - 8r
- Add 8r to both sides: r + 2 = -3
- Subtract 2 on both sides: r = -5
<u>Step 3: Check</u>
<em>Plug in r into the original equation to verify it's a solution.</em>
- Substitute in <em>r</em>: -5 + 2 - 8(-5) = -3 - 8(-5)
- Multiply: -5 + 2 + 40 = -3 + 40
- Add: -3 + 40 = -3 + 40
- Add: 37 = 37
Here we see that 37 does indeed equal 37.
∴ r = -5 is a solution of the equation.
<u>Step 4: Define equation</u>
-4x = x + 5
<u>Step 5: Solve for </u><em><u>x</u></em>
- Subtract <em>x</em> on both sides: -5x = 5
- Divide -5 on both sides: x = -1
<u>Step 6: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: -4(-1) = -1 + 5
- Multiply: 4 = -1 + 5
- Add: 4 = 4
Here we see that 4 does indeed equal 4.
∴ x = -1 is a solution of the equation.